Development of a Multi-Motor Asynchronous Electric Drive with Changes in the Coordinated Rotation of the Supply Voltages of the Motors - Kazhybek Tergemes; Nurgali Nalibayev; Algazy Zhauyt; Altyn Besterekova; Rassim Nigmatullin; Olga Zhivayeva; Irina Kazanina (Applied Sciences)
This study considered the issue of increasing the synchronizing capacity of a system for the coordinated rotation of asynchronous motors. Electromechanical relationships were obtained for changes in the value of the supply voltage of individual motors, the total rotor resistance (Ra), and the angular positions of the rotors (φ1, φ2, and φ3), with possible changes in angular misalignment. Additionally, we created an algorithm for calculating the currents and torques of the system’s motors within 0 and 90° and constructed the relevant mechanical characteristics. Ultimately, we developed various versions of multi-motor asynchronous electric drives with regulation and supply voltages (Un = 0.7 ÷ 1.0), featuring increasing and equalizing torques (Mn = 1.0 ÷ 1.4) in the system as a whole, along with the preliminary synchronization and synchronous braking of all motors.